Avaliação da redução do tempo de internação e da exposição à radiação e avaliação do impacto clínico do protocolo de Cintilografia de Perfusão Miocárdica estresseisolado comparado com o protocolo convencional estresserepouso: estudo prospectivo e meta-análise - Oliveira, Aline Ribeiro Nogueira de (2013)
Introduction: The Myocardial Perfusion Scintigraphy (MPS) is the noninvasive diagnostic method most accurate for the detection of obstructive Coronary Artery Disease (CAD) and for predicting outcomes in the short-term. One of the main applications of MPS is the identification of patients at risk who are treated in the Emergency Department (ED) with chest pain. Since the beginning of the MPS use, there were no significantly changes in protocols. It has been questioned recently the need of the rest phase in patients who have normal stress phase (perfusion and contractility). With current concerns about costs of examinations, length of stay in ED and radiation exposure, there is a growing interest in the protocol Stress-only. There are no records in the literature of meta-analysis about the prognostic value of stress-only protocol, as well as a prospective analysis with ED patients who had undergone to this protocol. Objective: To assess, through prospective study and meta-analysis, the time permanence reduction in ED, radiation exposure reduction and the clinical impact of Stress-only protocol compared with the conventional protocol (stressrest). Methods: 1) Meta-analysis: Statistical analysis of five articles selected though Systematic Review of the literature, that did prognostic evaluation of the stress-only protocol comparing it to the rest-stress protocol. 2) Prospective study: prognostic analysis of the stress-only protocol in patients admitted to the Pró-Cardíaco ED, with symptoms suggestive of CAD and stratified into low to moderate risk. Results: 1) Prospective study: 14 patients were studied. It was found a 50% (p=0,005) reduction in time of permanence in the ED and a 70.6% (p<0,001) reduction in radiation exposure. There were no reports of cardiovascular events or death in the follow-up period (180 days). 2) Metaanalysis: I2 statistic showed homogeneity between groups (I2 = 11.76), the Forest Plot graphic showed no significant difference between the two protocols (p = 0.48) and the Funnel Plot graphics showed no publication bias. Conclusions: Both studies, meta-analysis and prospective study, showed that the stress-only protocol is similar to the conventional protocol (stress-rest) in safety and accuracy